(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2016)
Restlessness and anxi ety problem of modern soci ety comes from individual psychological (internal factor) and from political and social factors such as di scriminati on and inj usti ce. To overcome those problems, i mpl ementi ng psychodynamic theory, behavi ori sm, humanism and multiculturalism are not enough. We are introduced to the fifth approach, that is, Islamic approach. The approach which is based on the belief, religious knowledge, and worship practices becomes the guidelines, techniques and destination Islamic counseling. The Islamic counseling is aimed at preventive, curative, rehabilitative development, using spiritual methods which are based on the counselee. Spiritual methods with techniques of spiritual practice, establish compassion, and reflection al Qudwah al-hasanah. Counselee-centered method is done by discussion and advice according to the counselees’ interests and values. A counselee is free to choose, plan, decide the behavior and values that are meaningful to him.